Penciptaan Cocktail Dress “The Radiant Treasure of Khatulistiwa” dengan Teknik Beading dan Draping - Nursabilillah, Ikrima; Marlianti, Mira; Suharno, Suharno (Mahesa Research Center, 2025)
The background to the creation of this cocktail dress was the direct appointment of the national director of Miss Teenager Indonesia to the author to create a cocktail dress that contained Indonesia's natural wealth. This request was executed by combining Indonesian culture and natural wealth elements in one unified cocktail dress collection, The Radiant Treasure of the Equator. This mix and match is a form of novelty because, de facto, in general, cocktail dress designers have not placed elements of Indonesian culture and natural wealth as the main theme of creating cocktail dresses. Therefore, the aim of creating this work, apart from fulfilling the Miss Teenager Indonesia 2024 event, is to offer a new cocktail dress that combines elements of Indonesian culture and natural wealth. To achieve this goal, the creation method is the one diamond model adopted from the double diamond model. The results of this creation are 4 (four) cocktail dress looks which were presented at the Miss Teenager Indonesia Grand Final at the Surabaya Youth Hall building on November 1, 2024.